If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + 20 = -2a + 40 Reorder the terms: 20 + 3a = -2a + 40 Reorder the terms: 20 + 3a = 40 + -2a Solving 20 + 3a = 40 + -2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2a' to each side of the equation. 20 + 3a + 2a = 40 + -2a + 2a Combine like terms: 3a + 2a = 5a 20 + 5a = 40 + -2a + 2a Combine like terms: -2a + 2a = 0 20 + 5a = 40 + 0 20 + 5a = 40 Add '-20' to each side of the equation. 20 + -20 + 5a = 40 + -20 Combine like terms: 20 + -20 = 0 0 + 5a = 40 + -20 5a = 40 + -20 Combine like terms: 40 + -20 = 20 5a = 20 Divide each side by '5'. a = 4 Simplifying a = 4
| 1+y-6y=y-8y+17 | | 4x^2+500x=0 | | -20=2y+2 | | 4e^6x-16e^3x-9=0 | | -7w-6=-4(w-3) | | 9(w-2)=7w-38 | | 9v+32=5(v+8) | | 4(y-9)=-9y-49 | | 3-3*6-3=x | | -6u+18=-3(u+1) | | y^2(y+5)-16(y+5)=0 | | 2y+3y=-15 | | -9x+19x=220 | | 3-3*2+1= | | 4x+2=-12+50 | | 3m-15-5n+mn=0 | | V=BQU | | 1x+1x+10+40=180 | | 90x-15=15(6c) | | 3x-7(4+2)=-x+2 | | 3(4x+1)-2(3x-4)=1 | | p+18=36 | | 3(4h+6)+2(-6h+9)=(h+2) | | x=-3.5+-0.5y | | S=7(3.72)vk+7(3.72)v^2 | | -2=4-3y | | 5.5+4= | | 12x-44-15x=140+80x | | 3x^2+31x-6.1=0 | | 21=9x-33 | | t(-8t^2+16)=0 | | 12x-44-15x=7+4x |